2021
DOI: 10.1002/ppul.25666
|View full text |Cite
|
Sign up to set email alerts
|

Zinc status and growth in infants and young children with cystic fibrosis

Abstract: Background: Zinc deficiency is associated with poor growth in children without cystic fibrosis (CF), but its impact on growth in children with CF is unknown.Objective: To determine the prevalence of low serum Zn (sZn) and its relationship with growth in the first 3 years of life in children with CF.Methods: We utilized data from infants with CF who were enrolled in a longitudinal study of nutrition and lung health and had sZn measured as part of clinical care.Cross-sectional correlations between sZn levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…A similar correlation was observed in adult asthma patients [ 26 ]. In lung fibrotic diseases, low serum zinc levels were related to increased infection rate and reduced overall growth, but not to tissue remodeling [ 16 , 17 ]. The problem of linking zinc deficiency to tissue remodeling in chronic airway diseases lies in the fact that zinc is essential for the enzymatic function of many proteins [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar correlation was observed in adult asthma patients [ 26 ]. In lung fibrotic diseases, low serum zinc levels were related to increased infection rate and reduced overall growth, but not to tissue remodeling [ 16 , 17 ]. The problem of linking zinc deficiency to tissue remodeling in chronic airway diseases lies in the fact that zinc is essential for the enzymatic function of many proteins [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is essential to the enzymatic activity of MMPs [ 11 ], and thus it is not surprising that zinc deficiency has been linked to fibrotic events in different organs including the lungs [ 12 , 13 , 14 , 15 ]. However, regarding fibrotic diseases of the lung, studies on the role of zinc deficiency or supplementation have been focused on its effect with regard to infection in cystic fibrosis [ 15 , 16 , 17 ]. Under experimental conditions, zinc deficiency increased inflammation and tissue remodeling in the lung [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown a dysregulation of zinc levels (lower in blood and higher in sputum) in adults and children with CF [ 25 , 58 , 86 , 87 , 88 , 89 ]. In the first three years of life, low serum zinc contents were detected in one-third of children with CF [ 86 ].…”
Section: The Role Of Zinc Dyshomeostasis In Lung Diseasementioning
confidence: 99%
“…Several studies have shown a dysregulation of zinc levels (lower in blood and higher in sputum) in adults and children with CF [ 25 , 58 , 86 , 87 , 88 , 89 ]. In the first three years of life, low serum zinc contents were detected in one-third of children with CF [ 86 ]. This study also found a discrepant link between growth and serum zinc in cross-sectional and longitudinal analyses; further study to better understand the role of zinc in growth in children with CF is warranted.…”
Section: The Role Of Zinc Dyshomeostasis In Lung Diseasementioning
confidence: 99%
“…Assessing zinc status in patients with cystic fibrosis is essential because, as underlined by Damphousee et al almost 25% of adults affected by cystic fibrosis, despite having a satisfactory nutritional status, have low levels of zinc in plasma correlated with worse clinical outcomes [ 119 ]. Similarly, Bauer et al identified low serum zinc levels in one-third of children with cystic fibrosis in the first 3 years of life [ 120 ]. Another interesting topic concerns zinc supplementation in extremely low-birth-weight (ELBW) infants (<1000 g) with chronic lung disease (CLD).…”
Section: Introductionmentioning
confidence: 99%